Fetal congenital anomalies among consanguineous and non consanguineous marriage pregnant women attending in Bangabandhu Sheikh Mujib medical university - Fatema, Kaniz; Zabin, Fahmida; Sultana, Nigar; Pervin, Hasna Hena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Consanguineous marriage has been described as an important factor contributing to increased congenital malformations. Congenital anomalies began to emerge as one of the major childhood health problems and refers to any malformations that occur in a developing fetus. The aim of the study was to assess fetal congenital anomalies among consanguineous and non-consanguineous pregnant marriages. Methods: An observational study design was adopted. Setting: Data were collected from the fetal medicine unit at Bangabandhu Sheikh Mujib medical university, Dhaka, Bangladesh during the period, from April 2017 to March 2018. Sample: A total sample was 100 pregnant women (Consanguineous and non-consanguineous with fetal congenital anomalies) were recruited according to certain criteria. Two tools were used as materials. Structured interview tool which entailed socio-demographic data; medical history, past obstetrical history, and ultrasonographic fetal assessment record. Results: More than half of the fetuses in the consanguineous marriage group had multiple affected systems compared to one-quarter of fetuses in the non-consanguineous marriage group (68 and 24% respectively). In this study highly statistically, significant differences were found in central nervous system anomalies, followed by genitourinary, musculoskeletal and nonimmune hydrops fetalis. Prevalence of hydrocephalus was higher in the consanguineous marriage group compared to the non-consanguineous group, while the frequency of hydronephrosis was higher in non-consanguineous marriage group than consanguineous marriage group. Ubiquity of non-immune fetal hydrops was also higher in the non-consanguineous marriage group. Conclusions: The most affected system of the fetus was CNS, followed by the gastrointestinal, urinary, and Musculoskeletal systems. Consanguineous couples are recommended to have genetic counseling, premarital examination, and screening about hereditary diseases.